Synthesis and physicochemical properties of UV-curable palm oil-based polyurethane reinforced with fluoroacrylate monomer - Mohamad Ismail, Mohamad Isa; Rasidi, Roslan; Nurjannah, Salim; Rohani, Mustapha; Siti Noor Hidayah, Mustapha (Springer Netherlands, 2024)
Functionalized monomer with specific chain length leads to different behaviors of UV-curable polymers. Due to the high demand for high-performance bio-based coating, this research was conducted to understand the effect of fluoroacrylate monomer (FAM) additions on physicochemical properties of palm oil-based polyurethane (POPU) coating. POPU oligomer was synthesized through a series of steps which was acrylation and isocyanation to form acrylated epoxidized palm oil (AEPO) and POPU oligomer, respectively. The POPU oligomer was further added with trimethylolpropane triacrylate and 1,6 hexamethyl diacrylate monomers at 60/30/10 wt% compositions respectively to form 100 wt% resin and followed by the addition of FAM at different concentrations (2–12 parts per hundred resin, phr). The sample was cast on a silicone mold at 1 mm thickness and cured under UV radiation for 60 s. The chemical structure elucidation was successfully done by NMR on AEPO and POPU. In 1H NMR analysis, C = C group was detected at 2.0–3.0 ppm and OH peak at 3.687 ppm. For POPU, peak at 3.0 ppm in 1H NMR analysis suggested that NH functional has formed. In 13C NMR, the existence of urethane linkage at 172 ppm further confirmed the reaction. The SEM and XRD results revealed that the addition of FAM induced separation between molecules, which lowered the crosslinking density of POPU coating. The thermal properties of POPU improved glass transition temperature (Tg) of the coating by 2.64% at the addition of 2 phr FAM. The physical properties of POPU was also improved as excellent adhesion properties of FPOPU was shown at 2–6 phr FAM addition: for glass (4B), wood (3B), and steel (5B to 4B). The hardness also improved across all substrates, such as glass (2H to 6H), wood (3H to 4H), and steel (7H to 8H). On the other hand, the addition of higher FAM concentrations (8–12 phr) showed a reduction in thermal properties as the Tg decreased by 7.54%. Moreover, physical properties of FPOPU also deteriorate as high concentration of FAM added. The hardness decreased for glass (6H to 3H) and steel (6H to 5H). Adhesion also decreased for all the substrates tested, including glass (3B to 2B), wood (3B to 2B), and steel (5B to 3B). The optimum FAM addition contributing to high adhesion, hardness and thermal performance was observed at 4 phr, and the best surface application was steel surface.